2016
DOI: 10.1007/s13193-016-0575-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging and the Use in Small Renal Masses

Abstract: The incidence of small renal masses (SRM) has been increasing, and this is mainly attributed to the incidental finding of such masses on imaging performed in asymptomatic patients. Consequently, this calls for careful evaluation and management of these masses to determine their nature and need for treatment. This article reviews current literature regarding the evaluation and management of SRM. It focuses on the specific use of MRI in the diagnosis and management of SRM. A Medline review of the literature was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Similarly, MRI can also result in the upgrade of renal cysts when using the Bosniak classification system due to excellent detection for the number of enhanced solid components (29,30). Andrew et al (31) performed a retrospective study, and the results revealed that it is easier to upgrade cyst complexity when using the Bosniak classification at the field strength of 3.0-T than 1.5-T.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, MRI can also result in the upgrade of renal cysts when using the Bosniak classification system due to excellent detection for the number of enhanced solid components (29,30). Andrew et al (31) performed a retrospective study, and the results revealed that it is easier to upgrade cyst complexity when using the Bosniak classification at the field strength of 3.0-T than 1.5-T.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MRI can also result in the upgrade of renal cysts when using the Bosniak classification system due to excellent detection for the number of enhanced solid components (29,30). Andrew et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty-seven percent of renal tumors have also been described as possessing a high possibility of malignancy. Renal tumors can be significantly differentiated using MR images to distinguish between malignant and nonmalignant tumors (3). Necrosis is among the factors that contribute to the generation of low intensity on T2-weighted MR images.…”
Section: Renal Tumorsmentioning
confidence: 99%